The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1186/s13072-018-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Consistent inverse correlation between DNA methylation of the first intron and gene expression across tissues and species

Abstract: BackgroundDNA methylation is one of the main epigenetic mechanisms for the regulation of gene expression in eukaryotes. In the standard model, methylation in gene promoters has received the most attention since it is generally associated with transcriptional silencing. Nevertheless, recent studies in human tissues reveal that methylation of the region downstream of the transcription start site is highly informative of gene expression. Also, in some cell types and specific genes it has been found that methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
284
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(325 citation statements)
references
References 88 publications
37
284
3
1
Order By: Relevance
“…Therefore, we selected these three regions for our analyses. Importantly, Anastasiadi et al 8 were looking at changes in gene expression associated with changes in DNA methylation distribution within promoters, gene bodies, and gene body sub-regions. Their results showed that in the cases where the association was significant, one could basically use mean or median value instead of looking a the distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we selected these three regions for our analyses. Importantly, Anastasiadi et al 8 were looking at changes in gene expression associated with changes in DNA methylation distribution within promoters, gene bodies, and gene body sub-regions. Their results showed that in the cases where the association was significant, one could basically use mean or median value instead of looking a the distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Although the methylation of gene promoters can potentially lead to the suppression of gene expression 1 , it has been shown that certain transcription factors actually require their binding sites to be methylated in order to promote binding 6 . In addition to promoters, DNA methylation within gene enhancer regions and gene bodies might also regulate gene expression 1,[7][8][9] . Thus, the function of DNA methylation is highly region-dependent and may vary from gene to gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, higher methylation levels in the gene promoters have been associated with transcriptional silencing (Illingworth and Bird, 2009; Straussman et al, 2009). However, gene expression inhibition have been related to other genomic features like the first exon and the first intron of the gene body not only in human (Blattler et al, 2014) but also in fish (Anastasiadi et al, 2018a). Further, the approach here performed for studying the methylation levels is limited to amplicons about ∼500 bp, that even with the intention of include promotor, first intron and first exon in the targeted regions, the entire gene body and possible enhancers involved in the gene regulation were not fully studied.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of cytosine residues within CpG dinucleotides is an important mechanism of variation and regulation in the genome 2932 . Cytosine methylation, particularly in the promoter region of genes, is often associated with a decrease in transcription 33 , and DNA methylation in the first intron and gene expression is correlated and conserved across tissues and vertebrate species 34 . Furthermore, modulation of methylation at CpG sites within the human genome can result in an epigenetic pattern that is specific to individual environmental exposures, and these may contribute to disease 26; 3537 .…”
Section: Introductionmentioning
confidence: 99%